2021
DOI: 10.2147/jir.s334642
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value of C-Reactive Protein/Platelet Ratio in Neonatal Sepsis: A Cross-Sectional Study

Abstract: Purpose: C-reactive protein (CRP) level and platelet (PLT) count have been demonstrated to be independent risk factor for neonatal sepsis. However, no data is currently available in regarding the association between CRP-to-PLT ratio (CPR) and neonatal sepsis. Methods: A total of 1048 neonates with suspected sepsis were enrolled in this study. Complete clinical and laboratory data were collected. CPR was calculated as CRP (mg/L)/ PLT (10 7 cells/L). Multivariate logistic regression analysis was performed to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 38 publications
1
13
0
1
Order By: Relevance
“…Infection markers such as PCT and CRP are commonly used for the adjuvant diagnosis of sepsis, 4 , 5 and their role in the diagnosis and prediction of sepsis is still being explored. 45 , 46 In this study, a diagnostic model by a combination of the four validated indexes and two infection markers was established, with the highest AUC‐ROC of 0.772 than that of PCT or CRP, although there were no significant differences between each combination AUC and AUC of PCT or CRP. B2M, VCAM1, and ApoE, besides ApoC3, already can be detected in clinical laboratory, which provided the clinical application possibility for septic diagnosis.…”
Section: Discussionmentioning
confidence: 96%
“…Infection markers such as PCT and CRP are commonly used for the adjuvant diagnosis of sepsis, 4 , 5 and their role in the diagnosis and prediction of sepsis is still being explored. 45 , 46 In this study, a diagnostic model by a combination of the four validated indexes and two infection markers was established, with the highest AUC‐ROC of 0.772 than that of PCT or CRP, although there were no significant differences between each combination AUC and AUC of PCT or CRP. B2M, VCAM1, and ApoE, besides ApoC3, already can be detected in clinical laboratory, which provided the clinical application possibility for septic diagnosis.…”
Section: Discussionmentioning
confidence: 96%
“…The combination of platelets and inflammatory biomarkers has been demonstrated to be associated with poor prognoses in a variety of clinical situations, including sepsis and cardiovascular diseases [34][35][36]. Li X found that a higher CPR was an independent risk factor for neonatal sepsis [11]. In addition, a previous study demonstrated that NLPR was associated with early acute kidney injury in cardiovascular surgery [31].…”
Section: Discussionmentioning
confidence: 98%
“…To date, numerous inflammation-related indices such as C-reactive protein (CRP), neutrophil-to-lymphocyte ratio (NLR) and fibrinogen (FIB), have been extensively used as prognostic values for many diseases [8][9][10]. Platelets play an important role in haemostasis and coagulation and are regulators of inflammation by controlling inflammation, and tissue integrity, as well as by defending against infection [11]. Some studies have indicated that patients with severe sepsis/septic shock have lower platelet count [12].…”
Section: Introductionmentioning
confidence: 99%
“…CRP is an acute inflammatory protein produced by the liver and significantly increases when there is inflammation or infection in your body. Studies have demonstrated that CRP was an important predictor and risk factor for sepsis and pneumonia [22][23][24][25][26]. ALB was the most abundant protein found in blood produced by the liver.…”
Section: Discussionmentioning
confidence: 99%